Fabrication of the (Y2O3:Yb–Er)/Bi2S3 composite film for near-infrared photoresponse1. Issue 11 (21st March 2015) - Jia, Hong; Ping, Chen; Xu, Cheng; Zhou, Jiajia; Sang, Xiangwen; Wang, Juechen; Liu, Chang; Liu, Xiaofeng; Qiu, Jianrong
<x xml:space="preserve">Abstract</x> Y2O3:Yb-Er/Bi2S3 composite films with photoactive current generation under NIR light excitation were fabricated by electro-deposition and a simple successive ionic layer adsorption and reaction (SILAR) method.